Effect of enriched environment on reproductive performance and body weight gain in Wistar rats (Journal of Laboratory Animal Science, 2019)
Environment is known to play an important role in animal health, reproduction and its growth. In order to understand the  influence of different kind of enrichment items on breeding performance and growth rate, this experiment was carried out  on Wistar rats. The male and female rats of mature age were randomly selected and these animals were provided with  different kind of enrichment items in cages such as fat rat hut, tunnel and crawl ball during the breeding period. Control  animals were not provided with any enrichment item in cages. Reproductive parameter (fertility index, survival success,  M/F ratio) were evaluated in all four group of animals. The results indicated that, the presence or absence of enrichment  items did not affect the reproductive performance and survival success of the pups. The pups continued to remain exposed  to the same kind of enrichment item, to evaluate the effect of enrichment on body weight gain. The male rats with fat rat  hut as an enrichment item showed significantly less body weight gain compared to control, whereas female rats with crawl  ball and tunnel as enrichment items showed significantly more body weight gain compared to that of control. The result of  this study indicates that, male and female may have different discrimination for enrichment items according to their shape,  size and surface area; however these enrichment items have no effect on reproductive parameter.
Keywords: Environmental enrichment; reproduction; rats